PELATIHAN PENGELOLAAN SDM ERA DIGITAL PADA UMKM KOTA PERDAGANGAN KECAMATAN BANDAR SUMATERA UTARA - Eska, Juna; Hidayatullah, Hidayatullah; Zulkhairani, Zulkhairani; Syahputra, Ronaldo (Smart Education, 2025)
Abstarct : One of the challenges faced by MSMEs in the era of digital economic change is the lack of human resource (HR) skills in adapting trading methods from conventional business models to online business models. The progress and complexity of digital changes that continue to increase every day offer many benefits for the progress of today's business world. The purpose of this service is to add knowledge to MSMEs in Perdagangan City kecamatan Bandar Sumatera Utara in overcoming challenges that arise due to changes in the digital era, especially in terms of Human Resources (HR) management. The methods in this service are lectures, discussions, and questions and answers as well as evaluation. This activity includes delivering information and understanding its tactics and effective techniques in managing human resources in the digital era. The results showed that participants felt satisfied because this activity helped them improve their ability to manage human resources in the modern era. Keywords : Human Resources; Digital Era; MSMEs Abstrak : Salah satu tantangan yang dihadapi oleh UMKM dalam era perubahan digital ekonomi adalah kurangnya keterampilan sumber daya manusia (SDM) dalam mengadaptasi metode perdagangan dari model bisnis konvensional ke model bisnis online. Kemajuan dan kompleksitas perubahan digital yang terus meningkat setiap harinya menawarkan banyak manfaat bagi kemajuan dunia bisnis saat ini. Tujuan pengabdian ini adalah untuk menambah ilmu pengetahuan kepada UMKM Kota Perdagangan kecamatan Bandar Sumatera Utara dalam mengatasi tantangan yang muncul akibat perubahan era digital, terutama dalam hal pengelolaan Sumber Daya Manusia (SDM). Metode dalam pengabdian ini yaitu ceramah, diskusi dan tanya jawab serta evaluasi. Kegiatan ini mencakup penyampaian informasi dan memahami taktiknya serta teknik efektif dalam mengelola SDM di era digital. Hasil kegiatan pengabdian ini menunjukkan bahwa peserta merasa puas karena kegiatan ini membantu mereka meningkatkan kemampuan mereka dalam mengelola sumber daya manusia di era modern. Kata Kunci: Sumber Daya Manusia; Era Digital; UMKM